Acute retinal necrosis secondary to Varicella Zoster Virus. (2019) - Vasudevan, Archana; Rojas-Moreno, Christian; Tarun, Tushar
Abstract: A 54 year old female presented to the ophthalmology clinic with pain and decreased vision in her left eye. No past medical history other than primary varicella zoster infection, in her childhood. The eye exam revealed a macular region with scattered areas of retinal opacity along with patches of necrosis on the periphery. She was started on valganciclovir and referred to the infectious disease clinic. Cell Count, blood chemistry and HIV were negative. Serum was sent for polymerase chain reaction (PCR) for Varicella Zoster Virus (VZV), Herpes Simplex Virus (HSV) and Cytomegalovirus (CMV). The VZV PCR was positive. She had decreased vision on the right eye two days later, and exam revealed peripheral retinal whitening. She was admitted and started on intravenous acyclovir. VZV is one of the most common causes of ARN and has been described in both immunocompetent and immunocompromised persons. Visual changes are usually noted weeks to months after the antecedent herpes zoster. Retinal involvement is bilateral in over half of cases, suggesting that VZV reaches the central nervous system hematogenously. The retinal exam reveals multifocal necrotizing lesions, often initially involving the peripheral retina. Therapy includes intravenous acyclovir with consideration of intravitreal foscarnet and other antivirals for progressing disease.